Die Kluft zwischen Wissenschaft und Kunsthandel - zum Status Quo und zur Zukunft eines Spannungsverhältnisses - Fuhrmeister, Christian 1963-; Klingen, Stephan 1958- (2023)
This article addresses the fundamental relationship – the gap – between the academic discipline (art history) and the art market. It is devoted to various aspects of this historical and contemporary coexistence and in particular examines the extent to which provenance research both has led and could potentially lead to – a new alliance amidst bipolar and dichotomous concepts. The basic parameters of the relationship between the academic world and the trade do not seem to be strongly affected by this forced marriage – forced since the government has requested it. However, due to their respective internal logic, provenance and art market research still have a certain »bridging potential«. This article also discusses the specific difficulties and asks the question: Who assumes responsibility for the basic research or the contextual research on National Socialism that is required by provenance research in museums and on the art market alike?
Keywords: Kunstgeschichte -- Fach; Kunsthandel